Doctor Retention in Ireland - What it may mean for the Global Health Workforce Reform Agenda; Comment on "Doctor Retention: A Cross-sectional Study of How Ireland Has Been Losing the Battle" - Bernard Hope Taderera (Kerman University of Medical Sciences, 2021)
The study of healthcare personnel migration in Ireland reports that most medical graduates plan to leave the country's health system. It may be possible to address this challenge by understanding and addressing the reasons why young doctors plan to leave. Future studies should contribute to the retention of early career doctors in high-income countries such as Ireland. This will help reduce the migration of doctors from low- and middle-income countries in order to address the global health workforce crisis and its impact on the attainment of universal health coverage in all health systems.